2021
DOI: 10.1039/d1nh00031d
|View full text |Cite
|
Sign up to set email alerts
|

In situ photoconductivity measurements of imidazole in optical fiber break-junctions

Abstract: We develop a method based on the mechanically controllable break junction technique to investigate the electron transport properties of single molecular junctions upon fiber waveguided light. In our strategy, a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…5(b)). Similarly, using a set of junctions based on alkyl thiolated molecules with different lengths and an identical HOMO-LUMO energy gap, photocurrents were observed under laser irradiation, and the magnitude of the rectification can be used further to provide an accurate evaluation of the enhancement effect of the plasmonic field on gaps of different sizes 55 . In addition to the alkyl chain molecules, the photocurrent generation mechanism in other single-molecule devices with smaller molecules that are difficult to excite under corresponding light irradiation is also considered to be photo-assisted tunneling.…”
Section: Photo-assisted Transport Mechanism Of Singlemolecule Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…5(b)). Similarly, using a set of junctions based on alkyl thiolated molecules with different lengths and an identical HOMO-LUMO energy gap, photocurrents were observed under laser irradiation, and the magnitude of the rectification can be used further to provide an accurate evaluation of the enhancement effect of the plasmonic field on gaps of different sizes 55 . In addition to the alkyl chain molecules, the photocurrent generation mechanism in other single-molecule devices with smaller molecules that are difficult to excite under corresponding light irradiation is also considered to be photo-assisted tunneling.…”
Section: Photo-assisted Transport Mechanism Of Singlemolecule Devicesmentioning
confidence: 99%
“…Figure reproduced with permission from: (a) ref 54 ,. Springer Nature; (b) ref 55 ,. American Chemical Society; (c, d) ref 56 ,.…”
mentioning
confidence: 99%
“…The molecular structure will be rearranged under the stimulation of light, resulting in a change in molecular conductance, which can be detected by single-molecule electrical platforms. [61,62] Therefore, when the molecular junction is exposed to light, different conductance can be obtained and used as an indicator for monitoring the photoreaction process. The study of photochemical reactions by single-molecule electrical platforms provides opportunities to explore the mechanism of photoreactions and visualize photochemical processes at the single-molecule level, and further enrich their appli-cations in the fields of synthesis, catalysis, and functional devices.…”
Section: Photoinduced Reactionsmentioning
confidence: 99%
“…The hydrogen atom bonded to the latter can be removed either in basic solutions or by exposing it to oxygen. , Apart from the extensive studies in biology and electrochemistry, imidazole is winning growing attention as an aurophilic anchoring group in single-molecule junctions. It has been experimentally confirmed that both the nitrogen atoms in the imidazole moieties address reliable binding sites to form stable single-molecule junctions with gold electrodes. Recently, we have reported that the Au–N bond is a donor–acceptor one when an imidazole molecule binds to the gold electrode via the pyridine-like nitrogen atom . In this case, the density of states (DOS) projected onto the imidazole molecule indicates that the LUMO is much closer to E F than the HOMO.…”
mentioning
confidence: 93%